Coming apart - Martin, Ann M. (New York : Scholastic, 2010)
Ruby works at odd jobs so she can buy a replacement for the cyrstal owl she has broken, the girls work on squares for a quilt, Flora becomes a volunter at Three Oaks and Nikki is nervous about her father's return as her parents plan to divorce.
Keywords: Secrecy -- Juvenile fiction; Families -- Juvenile fiction; Secrecy -- Fiction